Melanocortin 2, 3 and 4 Receptor Gene Expressions are Downregulated in CD8+ T Cytotoxic Lymphocytes and CD19+ B Lymphocytes in Rheumatoid Arthritis Responding to TNF‐α Inhibition. (July 2017) - Andersen, M.; Nagaev, I.; Meyer, M. K.; Nagaeva, O.; Wikberg, J.; Mincheva‐Nilsson, L.; Andersen, G. N.
Abstract: Melanocortin signalling in leucocyte subsets elicits anti‐inflammatory and immune tolerance inducing effects in animal experimental inflammation. In man, however, the effects of melanocortin signalling in inflammatory conditions have scarcely been examined. We explored the differential reactions of melanocortin 1‐5 receptors (MC1‐5R) gene expressions in pathogenetic leucocyte subsets in rheumatoid arthritis (RA) to treatment with TNF‐ α inhibitor adalimumab. Seven patients with active RA donated blood at start and at 3‐month treatment. CD4 + T helper (h) lymphocytes (ly), CD8 + T cytotoxic (c) ly, CD19 + B ly and CD14 + monocytes were isolated, using immunomagnetic beads, total RNA extracted and reverse transcription quantitative polymerase chain reaction (RT‐qPCR) performed. Fold changes in MC1‐5R, Th1‐, inflammatory‐ and regulatory cytokine gene expressions were assessed for correlation. Six patients responded to adalimumab treatment, while one patient was non‐responder. In all lymphocyte subtypes, MC1‐5R gene expressions decreased in responders and increased in the non‐responder. In responders, decrease in MC2R, MC3R and MC4R gene expressions in CD8 + Tc and CD19 + B ly was significant. Fold change in MC1‐5R and IFN γ gene expressions correlated significantly in CD8 + Tc ly, while fold change in MC1R, MC3R and MC5R and IL‐1 β gene expressions correlated significantly in CD4 + Th ly. Our results show regulation of MC2R, MC3R and MC4R gene expressions in CD8 + Tc ly and CD19 + B ly. The correlations between fold change in different MCRs and disease driving cytokine gene expressions in CD8 + Tc ly and CD4 + Th ly point at a central immune modulating function of the melanocortin system in RA.